Electron cloud spin generated by microring space‐time control circuit for 3D quantum printing. Issue 12 (18th June 2020) - Arumona, Arumona Edward; Punthawanunt, Suphanchai; Ray, Kanad; Phunklang, Sirigiet; Yupapin, Preecha
Abstract: A three‐dimensional (3D) quantum printing technique is proposed that uses electron spin cloud projections generated by microring‐embedded gold grating. A dark soliton pulse with a center wavelength of 1.50 μm excites the gold grating, leading to electron cloud oscillations. By using suitable parameters, the whispering gallery mode is obtained, which is the result of trapping light (electrons) inside the silicon microring. The plasma wave frequency is generated at the Bragg wavelength at which the electron density is obtained. The electron spin‐down and spin‐up forms the x‐axis and y‐axis along the propagation z‐axis. In this proposal, the propagation wave axis is applied to increase the printing resolution. The printing points are formed by the spin‐down, spin‐up, and no spin associated with [x, y, z] as [1, 0, −]. The electron spins are distinguished by the time sequence and by modulating with the Gaussian pulse of 1.30, 1.10, and 0.80 μm, from which the spin states of the electron can be detected and characterized. The shortest space‐time paradox gap is around 50 fs, which is the limitation of all measurements (observations). The electron transport spin projection is achieved with respect to the time function in which the 3D image is printed with a resolution of 50 fs (10 −15 s). In application, the trapped electron densities within the circuit are made possible via wireless connection for long‐distance transmission.